Microbiological and Physicochemical Approach in the Feeding of Superworm (Zophobas morio) with Petroleum-Derived Polymer Diets - Brandon R. Burgos; Fabiola Morales; Rodrigo Morales-Vera; Cristian Valdés; Jorge Y. Faundez; Eduardo Pereira de Souza; Flavio Henrique-Silva; Ariel D. Arencibia (Microorganisms)
Plastics are very versatile materials that have contributed to the development of society since the 19th century; however, their mismanagement has led to an accumulation of plastic waste in almost every ecosystem, affecting the fauna of the planet. However, recently, some studies have shown that some insects might be able to adapt, consuming a wide range of hydrocarbon base polymers. In this work, the adaptive capacity of Zophobas morio larvae when feeding on different synthetic polymers derived from petroleum was studied. Four different thirty-day larval feeding treatments were carried out with synthetic polymers, including expanded polystyrene (PS), low-density polyethylene (LDPE), polyisoprene (PI), and butyl rubber (BR); in addition, a positive control of organic diet was included. Intestinal bacteria were isolated from the treatments and identified by Sanger sequencing. To analyze the chemical composition and physical form of the frass produced, Fourier transform infrared spectroscopy (FITR) was performed, and images of the feces’ surfaces were taken with scanning electron microscopy (SEM), respectively. Zophobas morio larvae were able to consume 54% of PS in 30 days, equivalent to 3.2 mg/d/larva. Nine culturable bacterial strains associated with the decomposition of synthetic polymers were identified in the intestine of the larvae. As for the physicochemical analysis of the feces, FTIR spectra showed the scission of bands corresponding to functional groups of the synthetic polymers in the comparison of the plastic diet treatments versus the feces of antibiotic-treated and plastic-fed larvae, while the comparison of spectra of the plastic and control treatments also identified differences in the absorption peaks. SEM imaging demonstrated that superworm feces differed in dependence on the substrate consumed. The findings demonstrated that Zophobas morio larvae possess a gut biological complex that allows them to feed and survive by consuming various petroleum-derived polymers.